Manajemen Keamanan Siber Dalam Perlindungan Data Pada Layanan Aplikasi Transportasi Publik - Christoba Parulian S; Naufal Yusuf Dinda Fahreza H; Nur Aziz Raihan; Rayhan Dewanta Irwan R (Journal of Informatic and Information Security, 2024)
The digital era has massively transformed the public transportation system with the use of technology, but it also poses challenges in terms of cyber security. This study focuses on analyzing how cybersecurity management affects people's views on the safety and service quality of public transportation apps. The method used in this study is a quantitative approach, where data is collected through an online survey and then analyzed descriptively. The findings of this study show that cybersecurity management is highly influential on service quality in public transportation apps. Overall, users have a positive view of app security, even in the “Very Good” category. However, there are still some aspects that need to be improved, especially regarding the protection of personal data and awareness of cyber security. The results of this study will serve as a basis for formulating better security policies and strategies to increase public trust in public transportation services.